Spatial changes in zooplankton communities in a strong human-mediated river ecosystem - Czerniawski, Robert (PeerJ, 2018)
River damming causes a decrease in water current velocity which leads to an increase in richness and abundance of organisms atypical for running waters. Zooplankton is a representative example of such organisms. The influx of zooplankton from carp ponds is an additional factor that increases richness and abundance of zooplankton in rivers. We hypothesized that zooplankton dispersing from the carp ponds colonize the impoundments in river and the richness of zooplankton increase in impoundments by development of new species, not observed in the upstream. The zooplankton was collected monthly from April to September of 2013 and 2014. Sampling sites were located in the Barycz river (in the lotic sections and in the dam impoundments), as well as in its tributaries, which are the outlets of carp ponds. The most changes in zooplankton richness and abundance were observed at sites located within the dam impoundments, especially in relation to the lower values of the current velocity. Since the abundance of pelagic rotifers, cladocerans and copepods in the carp pond outlets was similar to that at lower sites in the Barycz, the influence of the carp pond outlets on the abundance in the dam and lotic sections was significant. The river itself in its impounded sections provides advantageous conditions for retention and colonization by a high abundance of zooplankton dispersing from the carp ponds, and for the development of species not occurred in the upstream, which, in turn, increases richness.